Contractor business strategy decision in competitive bidding: case studies - Ngan , Kwong Yoong; Othman, Omar; Omran, Abdelnaser; Bakar, Abu Hassan Abu (2008)

(untitled)
The purpose of this paper is to examine the relationship between relevant parties and contractors regarding the bidding decision during bidding process. The game theory can be a tool for contractors’ business decision. This paper will define the business strategies that are demonstrated by contractors and the bidding decision was determined by using the bid model based on game theory. A company might win a tender over its competitors basically because other competitor has submitted the dangerously lowest price or higher price. The bidding process us crucial problem for contractors because involving the complicated decisions and strategies. Bid / no bid decision and mark-up price/ bid price would be two critical items for contractors. Four (4) case studies been conducted and a game tree/ decision tree analysis on their current business strategies were undertaken. It is proposed that a bid model (game theory) would be able provide a systematic support system to help the contractors define their business strategies decision in competitive bidding.